(3UMjM eSdes - (3eSde Hf GdMLGL Hf eSde GdbTjQj GdfjSGHhQqi, CHh GdMSjf, CHh GdMSjf,J (B261 (3g` s ((3YHO Gddg Hf YajQ GdCfOdSi s)
(3ChdgG (B:s
(3bGd GdbTjQi GdfjSGHhQi QVi Gddg Yfg GdMeO ddg QH GdYGdejf CeG HYO Efc UeeJ HGdaMU Yf JYQa LedI GdCNHGQ GdeCKhQI Yf QShd Gddg Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3jfJgi HHGH fRhd JMQje GdNeQ Hbhdg (B: (3Yf bjS Hf YHGO SeYJ CHGPQ jbSe GfRdJ HeKd MOjK eSde s
(3UMMgG hcJH HghGeTgG TQhMkG hJYdjbGJ GdMGaX CHh HcQ Hf NjQJ SfI (B575 (3haQZ GHf NjQ ef ebGHdJgG hJUMjMgG SfI (B574s
(3ef JMHjS GdNdjaI HaGS Ydi Hf GdSdWGf eMeO Hf YHO Gddg YGe (B1181 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B221 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B232s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg , JQeje s
Keywords: (3GdMOjK h GdeUWdMs